Modeling and control design simulations of a linear flux-switching permanent-magnet-levitated motor - Rafal P. JASTRZEBSKI (The Japan Society of Mechanical Engineers, 2017)
For flux-switching PM (FSPM) motors, permanent magnets (PMs) are placed in the stator and not in the rotor structure as in the majority of PM motor designs. Recently, FSPM bearingless motors have been developed for special applications. The FSPM concept can be adapted to linear motors. For linear motors, magnets or windings located on the mover significantly decrease the complexity and cost for longer tracks. Following the ideas from the rotating bearingless motors, this work focuses on combining the motoring and levitation functionalities in a linear machine. Still, to separate the controls of air gap and torque (thrust), two sets of windings or multiphase windings are required for both rotating FSPM and linear PM machines. A linear FSPM-levitated motor solution, which integrates the magnets, winding structure, and all the driving and control electronics on the mover is desired in many applications. However, because of electromagnetic unbalances, the machine design is intertwined with the control limitations and requirements. We propose a modeling methodology for accurate derivation of the machine dynamic and static force parameters as a function of air gap, control currents, and track position in an extended operating range. Model-based control simulations based on accurate plant models determine the achievable machine performance and levitation limitations. The design and modeling methodology is universal and can be applied to various PM bearingless motors and magnetic levitation systems. In the case study of a linear FSPM-levitated motor (mover), air gap control is possible in a manner equivalent to classical active magnetic bearings, where it is linearized and independent of the thrust control.